Analysing financial performance of listed cement industries in Nigeria: Financial Ratio Approach - Olayinka, Aminu Abdulrahim; Mustapha, Shettima (Annals of Management and Organization Research, 2022)
Purpose: The grounds for this study are to reflect a quantitative connection allying the financial statements of different firms at different periods and how the financial performance (FP) of firms can be measured using financial ratios. Research methodology: This research employs descriptive research with a quantitative approach focusing on calculations. Data were analysed through the Financial Ratio Analysis (FRA). Results: The comparative FRA unlocks the overall FP of the three firms. The result refill that, on average, Dangote Cement plc maintain the lead, CCNN/BUA Cement second, while Lafarge Africa plc is the least in all the FP indicator used. Limitations: The analysis is restricted to ten years FSs published by the three giant firms in the cement industries in Nigeria plc between the years 2012 to 2021. Contribution: This analysis expatriates and, in greater detail, the benefits that can be derived from applying FR analysis as a tool for financial performance (FP) measurement. It also helps in determining how the financial performance of firms can be measured through financial ratios.